Comparison of Lintula Score with Modified Alvarado Score for Diagnosing Acute Appendicitis in Adults - Pun, Ashis; Rayamajhi, Akin Jung; Neupane, Dipendra (Journal of Nepal Health Research Council, 2024)
Background: Acute inflammation of the appendix or acute appendicitis is one of the most prevalent surgical emergencies seen in day-to-day practice. The delay in the diagnosis and the treatment of the condition can lead to complications and even death. Various scores have been developed over the time for aiding the diagnosis of Acute Appendicitis. Methods: A hospital based cross-sectional study was conducted in Bharatpur hospital of Chitwan district of Nepal from December 30, 2020 to December 29, 2022 .This study identified and enrolled acute appendicitis patients that were treated in a tertiary hospital’s emergency department of Bharatpur. The data were obtained and used to calculate modified Alvarado, and Lintula scores. All the patients were categorized into two groups according to their histopathological results, i.e., positive appendectomy and negative appendectomy. The sensitivity and specificity of different scoring systems in diagnosing Acute appendicitis was investigated. Results: Sensitivity and specificity of Modified Alvarado score were 89.2% and 80.0% respectively. Diagnostic accuracy of Modified Alvarado Score was 88.57%. Positive productive value and Negative productive values of this scoring tool were 98.3% and 36.3% respectively whereas, diagnostic accuracy of Lintula score was 75.0%. Conclusions: It can be inferred from the study that Modified Alvarado Score is a good screening tool for diagnosing need of appendectomy. Keywords: Acute appendicitis: lintula score; modified alvarado score.